Prevalence of abnormal thyroid hormone levels in acute new-onset atrial fibrillation - Hytting, Jakob; Celik, Serkan; Bodeström Eriksson, Linus; Mallios, Panagiotis; Digerfeldt, Christofer; Waldemar, Annette; Wijkman, Magnus; Singull, Martin; Hubbert, Laila (Frontiers in Cardiovascular Medicine, 2025)
IntroductionKnown risk factors for new-onset atrial fibrillation/flutter (NOAF) include thyrotoxicosis and subclinical hypothyroidism. While prior research has predominantly explored the link between thyrotoxicosis and NOAF, the presence of subclinical hypothyroidism among patients presenting with acute NOAF in the emergency department (ED) remains an underexplored area of inquiry. This study aimed to assess the prevalence of undiagnosed thyrotoxicosis and subclinical hypothyroidism in patients with acute NOAF diagnosed in the ED.MethodsThis registry-based cohort study was conducted in the ED at Vrinnevi Hospital in Sweden during the years 2018, 2020, and 2022, with a 1-year follow-up period. Patients ≥18 years diagnosed with NOAF in the ED, with no ongoing thyroid hormone substitution or previous documented thyroid abnormality within the past 2 years, were included. The primary outcome was the diagnosis of thyrotoxicosis or subclinical hypothyroidism either in the ED or during a 1-year follow-up period.Results486 patients with NOAF were included in the study (43.6% females). 329 (67.7%) underwent thyroid function testing in the ED or by the end of the 1-year follow-up. In total, 16 (4.9%) patients presented with subclinical hypothyroidism while 4 (1.2%) patients presented with clinical or subclinical thyrotoxicosis.DiscussionThis study found that subclinical hypothyroidism was more prevalent (4.9%) than thyrotoxicosis (1.2%) among patients presenting with acute NOAF. These findings contrast with previous research that has predominantly linked thyrotoxicosis with acute NOAF, suggesting the need for further studies including both subclinical hypothyroidism and thyrotoxicosis in patients with NOAF.